Immunomodulatory and Anti-fibrotic Effects Following the Infusion of Umbilical Cord Mesenchymal Stromal Cells in a Critically Ill Patient With COVID-19 Presenting Lung Fibrosis: A Case Report - Silva, Kátia Nunes da; Pinheiro, Priscila Carvalho Guedes; Gobatto, André Luiz Nunes; Passos, Rogério da Hora; Paredes, Bruno Diaz; França, Luciana Souza de Aragão; Nonaka, Carolina Kymie Vasques; Barreto-Duarte, Beatriz; Araújo-Pereira, Mariana; Tibúrcio, Rafael; Cruz, Fernanda Ferreira; Martins, Gabriele Louise Soares; et al. (Frontiers in Medicine, 2021)
Background: Coronavirus disease 2019 (COVID-19) associated- severe acute respiratory distress syndrome (ARDS) patients may require prolonged mechanical ventilation which often results in lung fibrosis, thus worsening prognosis and increasing fatality rates. Mesenchymal stromal cell (MSC) therapy may decrease lung inflammation and accelerate recovery in COVID-19. In this context, some studies have reported the effects of MSC therapy for patients not requiring invasive ventilation or during the first hours of tracheal intubation. However, this is the first case report presenting reduction of not only lung inflammation but also lung fibrosis in a critically ill long-term mechanically ventilated COVID-19 patient. Case presentation: This is a case report of a 30-year-old male COVID-19 patient under invasive mechanical ventilation for 14 days in the ICU, who presented progressive clinical deterioration associated with lung fibrosis. Symptoms onset was 35 days before MSC therapy. The patient was treated with allogenic human umbilical-cord derived MSCs [5 x 107 (2 doses 2 days interval)]. No serious adverse events were observed during and after MSC administration. After MSC therapy, PaO2/FiO2 ratio increased, the need for vasoactive drugs reduced, chest CT scan imaging, which initially showed signs of bilateral and peripheral ground-glass, as well as consolidation and fibrosis, improved, and systemic mediators associated with inflammation and fibrosis decreased. Modulation of different cell populations in peripheral blood was also observed, including a reduction in inflammatory monocytes and an increase in frequency of patrolling monocytes, CD4+ lymphocytes and type 2 classical dendritic cells (cDC2). Patient was discharged 13 days after cell therapy. Conclusions: MSC therapy may be a promising option in critically ill COVID-19 patients presenting both severe lung inflammation and fibrosis. Further clinical trials could better assess the efficacy of MSC therapy in critically ill COVID-19 patients with lung fibrosis associated to long-term mechanical ventilation.